Battery Charger Design with PI Control Based on Arduino Uno R3 - Agung Prasetyo Utomo; Anggara Trisna Nugraha Angga; Dwi Sasmita Aji Pambudi; Dadang Priyambodo (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2021)
In line with the increase in the electrification ratio target to 100% in 2025, the electricity demand is projected to increase more than 7 times to 1,611 TWh in 2050. the share reached 58% or about 50 GW. On the other hand, the current energy diversification carried out by the government is directed at the utilization of renewable energy that exists in nature. One of the important components in this power plant is the battery. This is because the battery functions as a store of energy generated from the vertical wind turbine. After use, the battery needs to be recharged. The process of recharging the battery that is not suitable can cause a decrease in battery performance. Therefore, in the process of charging this battery, a safe battery charging system is needed for the battery to maintain battery performance and extend battery lifetime. This battery charging system uses a PI control system. From the research that has been done, it was found that. From the research that has been done, it is found that the output voltage value of the battery charger that is made has an average error percentage of 1.373% and the power output efficiency of the battery charger is 83-95%.